The becoming of business bodies: Gender, appearance, and leadership development. Issue 1 (February 2013) - Kelan, Elisabeth K
The article uses media images of businesswomen to explore how Master of Business Administration students position themselves in relation to the businesswomen. Following feminist media studies, the article argues that subjects are "becoming" through media images. In order to explore subject formation processes through images, a business school setting, as a place that develops future leaders and that is dominated by men and masculinity, was chosen. The analysis of the interviews indicates that Master of Business Administration students position themselves in relation to the images of businesswomen by commenting on the appropriateness of dress based on the industry and by discussing that being sexually attractive is deemed unprofessional for women. While the subject positions that the Master of Business Administration students occupied were rather normative in nature, the article argues that images can be used as a helpful tool to allow reflection on normativity in relation to gender in leadership development. It is thereby possible to think about a displacement of norms by facilitating the use of alternative subject positions.